PENGARUH PENGGUNAAN MEDIA EDUTAINMENT TERHADAP MINAT BELAJAR DAN KEMAMPUAN NUMERIK PESERTA DIDIK SMP KELAS VII DI MASA PANDEMI COVID-19 - Nur Faizah; Sarwo Edy; Fatimatul Khikmiyah (Universitas Muhammadiyah Makassar, 2023)
This study aims to determine the influence of the use of edutainment media on interest in learning and the numerical abilities of VII grade junior high school students in the even semester of the 2021/2022 academic year. This research is a correlational study with a quantitative approach. The population in this study were class VII students at 5 junior high schools in the Gresik District, totaling 702 students. The sample used in this study were 254 students who were obtained using the slovin formula with the proportionate cluster random sampling technique with an error rate of 5%. The instruments used in this study were tests of the ability to use edutainment media, tests of students' numerical abilities, and questionnaires of students' learning interest. The data analysis test used is Structural Equation Modeling (SEM) using the Amos 24 program. The results of this study indicate that: (1) There is a positive and significant influence between the use of edutainment media and students' learning interest. (2) There is a positive and significant influence between the use of edutainment media and students' numerical abilities. (3) There is an influence between learning interest and students' numerical abilities.Keywords: Edutainment Media, Learning Interest, Numerical Ability